Surface-enhanced Raman spectroscopy for identification and discrimination of beverage spoilage yeasts using patterned substrates and gold nanoparticles. (November 2017) - Uusitalo, Sanna; Popov, Alexey; Ryabchikov, Yury V.; Bibikova, Olga; Alakomi, Hanna-Leena; Juvonen, Riikka; Kontturi, Ville; Siitonen, Samuli; Kabashin, Andrei; Meglinski, Igor; Hiltunen, Jussi; Laitila, Arja
Abstract: In the beverage industry, the detection of spoilage yeasts such as Wickerhamomyces anomalus and Brettanomyces bruxellensis can be labourious and time-consuming. In the present study, a simple and repeatable technique was developed for rapid yeast detection using a combination of patterned gold-coated surface-enhanced Raman spectroscopy (SERS) substrates and gold nanoparticles. W. anomalus and B. bruxellensis showed several characteristic peaks, enabling the discrimination of these yeasts without chemometric analysis. The control yeast used as an indicator yeast, Rhodotorula mucilaginosa, showed 7 cell wall-related peaks originating from lipids and haemoproteins. Analysing W. anomalus SERS spectra with differently sized and shaped gold nanoparticles revealed the benefit of using either large, spherical, chemically synthesised gold nanoparticles or small, laser-synthesised, gold-silicon nanoparticles for yeast detection. Additionally, the spectra showed differences in SERS signal construction for small molecules and biological cells, as the nanoparticles with best response in biological cell detection did not excel in small molecule detection. The use of small composite gold-silicon nanoparticles in combination with the SERS substrate gave distinctive spectra for all detected yeast species. Highlights: A simple and rapid method for yeast identification with NIR SERS was developed. Beverage spoilage yeasts were discriminated through several characteristic peaks. The size, shape and media of nanoparticles had crucial effect on the SERS signal. Gold-silicon composites with SERS substrate gave most distinctive yeast spectra.